FINANCIAL EVALUATION OF BROILER PRODUCTION PROJECTS IN DIYALA GOVERNORATE IN THE YEAR 2017 - & et al., Mahmood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research aims to study the economic evaluation of meat Broiler projects province of Diyala for 2017 by identifying the economic merit of the production projects of the meat broiler by applying some economic evaluation criteria using questionnaire form. Data were collected randomly from a sample of 40 meat Broiler breeders representing 20.41% of  total 196 poultry fields which established in Diyala Governorate. The sample was divided into three categories: the first category was 21 breeders, the second category was 15 breeders, the third category was 4 breeders, and the design capacity of each category (1-50) thousand Broiler, (51-100) thousand Broiler, more than 100 thousand Broiler respectively. The results showed that the producers at the sample level achieve an annual profit of 5.5 Billion  ID, while the return of the invested dinar at the level of categories represented in the first category which gave the highest value, as follow 1.594, 1.504, 1.395 ID for the first category and second category and third category respectively, which indicates to efficiency of the studied projects while the payback period of the capital was estimated to be about 1.650, 1.939, 2.456 years for the three categories respectively, The results showed that most of the production costs were variable. The fixed costs constituted only about 10.25% of the total cost. The feed value accounted for more than half of these costs by 65.89% of the total cost, followed by the value of the chicks by 18.56%  then others costs. The fixed costs included the field rent by 17.82%, while the permanent work was 12.16%. The interest of capital was the largest percent by 70.02% of the total fixed costs. Therefore, it is recommended that the state should intervene directly and adopt an effective and vital policy. In supporting and encouraging breeders by providing them with feed and protein concentrates for their fields at subsidized prices.